Availability and use of educational databases for effective teaching and learning by academic staff - Aliyu, Jafaru Shinkafi; Gadanga, Aliyu Tsafe (Record and Library Journal, 2024)
Background of the Study: Educational database also known as academic database or online databases as collection of electronic information resources produced by publishers on various disciplines of human knowledge. These databases, plays a pivotal role in streamlining operations enhancing educational quality and ensuring efficient communication in institutions of learning at all levels. Purpose: The purpose of the study is to determine the availability of educational databases in Usmanu Danfodiyo University, Sokoto as well as determine the extent to which these resources are utilized by academics in the study area. Method: Quantitative research approach using descriptive design was used involving 254 academics in Usmanu Danfodiyo University, Sokoto as sample respondents. Findings: Findings of the study shows that there are several kinds of educational databases in the university. It further revealed that the most frequently used databases by academics in Usmanu Danfodiyo University, Sokoto are Pavilion, HINARI, Elsevier, Science Direct and DOAJ amongst others with a high extent of mean score ranging between 2.75-3.07 and SD= of .82-.96. These are above the 2.50 accepted average ranges. On extent of use, the findings revealed a high extent of the mean of 2.76-2.95 and SD= of .85-.1.0 which are both above the 2.50 accepted average mean. The Cluster of mean of 2.83 shows the extent of utilization of databases. Conclusion: The study concludes that the use of educational databases by academic staff contributed immensely towards effective teaching and learning in Usmanu Danfodiyo University, Sokoto.